Polymer-Directed Crystallization of Luteolin, Quercetin, and Myricetin - Kim, Hyeongju; Kim, Jeongeun; Kwon, O. Pil; Lee, Jonghwi (Macromolecular Research, 2020)
for active pharmaceutical ingredients, the bioavailability, stability, and processability critically depend on crystal habit and size. The presence of polymers in a crystallization solution can engineer broader ranges of crystal habit and size, but only in certain cases. To elucidate the underlying mechanism of this selectivity, polymer-directed crystallization was systematically investigated here for a series of natural polyphenols, namely luteolin, quercetin, and myricetin. Significant changes in crystal habit and size were observed in the cases of quercetin and myricetin. Peak broadening in X-ray diffraction profiles and significant amounts of polymer within the crystallized particles suggested possible composite structure formation via a non-classical crystallization mechanism. Polyethyleneimine and poly(vinyl alcohol) showed relatively stronger crystal engineering effects than poly(ethylene glycol). The results facilitate understanding of the specific interactions important for crystal engineering and thus preparing polyphenols to attain wide ranges of habit and particle size for various applications. [Figure not available: see fulltext.].
Keywords: Active pharmaceutical ingredients; Crystallization mechanisms; Crystallized particles; Directed crystallization; Peak broadening; Polyethyleneimine; Specific interaction; X ray diffraction profile; antioxidant; luteolin; mesocrystal; myricetin; polyphenol; quercetin